(untitled) (International Journal of Nursing Education, 2020)
Introduction: Transition of adolescents with intellectual disabilities into adulthood is a concern to caregivers and the society at large. Transition is still a challenge to health care and non-health care system. Studies on legal and ethical issues have been done regarding the care, treatment and treatment of adolescents with intellectual disabilities. Strategies for transitioning of these adolescents have not been given a priority. Purpose: To develop strategies for transition of adolescents with intellectual disabilities into adulthood. Method: A sequential exploratory mixed method was undertaken with 149 caregivers as participants informed the development of the strategies for transitioning from adolescence to adulthood. Multiple data collection method including individuals interviews, focus group and survey questionnaires were used to arrive at the findings. Results: Five main themes emerged from the analysis as transition possibility, the role of different stakeholders, the provision and development of working skills, caregivers’ knowledge and understanding of guidelines and alterations to adapt to changes. Conclusion: The findings of this study indicated that the majority of caregivers working with adolescents with intellectual disabilities do not have the skill to effectively care for them. Hence, the developed strategies would provide caregivers with knowledge and skill to improve the care of adolescents with intellectual disabilities.